Verapamil does not modify catalytic activity of CYP450 in rainbow trout after long-term exposure - Burkina, V; Zamaratskaia, G; Randák, Tomáš; Li, Z H; Fedorova, G; Pickova, J; Žlábek, Vladimír (Ecotoxicology and environmental safety, 2012)
Little is known about the effects of the cardiovascular drug verapamil (VRP) on metabolic processes in fish. Most calcium channel blockers including VRP are metabolized by cytochrome P450 (CYP450) enzymes. In this study we investigated the in vivo effect of VRP on some CYP450-mediated reactions in juvenile rainbow trout (Oncorhynchus mykiss). Fish were exposed to sublethal concentrations of VRP (0.5, 27 and 270 μg l(-1)) for 0, 21, and 42 day. The following CYP450-mediated reactions were studied in hepatic microsomes: O-dealkylation of ethoxyresorufin, methoxyresorufin, and pentoxyresorufin, hydroxylation of coumarin, tolbutamide, and p-nitrophenol, and O-debenzylation of 7-benzyloxy-4-trifluoromethylcoumarin. The amounts of products of these reactions did not differ among fish exposed to different levels of VRP and control fish. This suggests that the levels of VPR used did not alter catalytic activity of the selected CYP450 enzymes. In conclusion, none of the investigated CYP450-mediated reactions has potential as a biomarker to monitor VRP contamination of the aquatic environment.
Keywords: Microsomes, Liver; chemické látky znečišťující vodu; Oncorhynchus mykiss; biologické markery; Nitrophenols; Biomarkers; Coumarins; vztah mezi dávkou a účinkem léčiva; Water Pollutants, Chemical; blokátory kalciových kanálů; Verapamil; systém (enzymů) cytochromů P-450; Animals; Calcium Channel Blockers; Oxazines; játra; Cytochrome P-450 Enzyme System; zvířata; nitrofenoly; oxaziny; kumariny; Liver; Dose-Response Relationship, Drug; jaterní mikrozomy; verapamil